Intraoperative Radiation “Boost” to the Surgical Resection Bed following Pancreaticoduodenectomy for a Borderline Resectable Pancreatic Carcinoma: A Case Report - Thomas, Tarita O.; Small, William; Fleming, Mark; Kang, Song; Hoefer, Richard A. (Frontiers in Oncology, 2018)
Neoadjuvant therapy including chemotherapy alone or concurrent chemotherapy with external bream radiation is a standard treatment strategy for borderline resectable pancreatic adenocarcinoma and is also used routinely for primary operable cancers at some institutions1. The use of intraoperative radiation therapy (IORT) has been limited largely because of the logistical issues in delivery of radiation during surgery2. This is the first reported case of a borderline resectable pancreas cancer patient who underwent neoadjuvant chemo-radiation therapy followed by resection with the use of IORT using the mobile IntraBeam Device to boost the resection bed and improve local control by dose escalation.